Presentation Skills for Students - Van Emden, Joan.; Becker, Lucinda M., 1963- (Basingstoke : Palgrave Macmillan, 2004)
The ability to speak clearly, fluently and persuasively is essential to students in all courses of study. This text discusses a wide range of speaking occasions, such as giving a seminar or a project presentation.
Includes bibliographical references (p. 139) and index.
Keywords: Public speaking; Forums (Discussion and debate); Literature